Analisis Jual Beli Chip dalam Game Online High Domino Menurut Perspektif Ekonomi Syari’ah Kasus di Kecamatan Leuwisadeng Bogor - Ahmad Gettarindo; Ikhwan Hamdani; Nurman Hakim (IAI Nasional Laa Roiba Bogor, 2024)
At this time, a new phenomenon emerged in society, namely many people buying and selling using the results of a game. An example is in kp. Peutey Leuwisadeng Village, Leuwisadeng District, Bogor Regency. Even though the results obtained are only coins from the Higgs Domino game, these coins can be traded as additional income to meet daily needs. This research is focused on three things, namely the system of buying and selling chips in kp. Peutey Leuwisadeng Village, Leuwisadeng District, Bogor Regency and buying and selling chips in the Higgs Domino game in the perspective of Islamic economics and the mechanism for playing the high domino game. In this study, the authors used qualitative methods by conducting observations, interviews, and documentation to collect field data and apply empirical laws, namely laws taken from human behavior. the aim is to strengthen the research. The results of the study show that at kp.peutey Leuwisadeng Village, Leuwisadeng District, Bogor Regency, the system of buying and selling chips in the Higgs Domino game is carried out by meeting face to face or sending chips in advance to the buyer's account. The money is usually paid by transfer or taken directly by chip collectors who then resell them at a higher market price. Although this practice is common, buying and selling chips in the Higgs Domino game is considered haram because it originates from betting and gambling which is punished as an element of maysir. In Islamic economics, buying and selling conditions do not contain elements of maysir, gharar and usury. Therefore, the practice of buying and selling chips in the Higgs Domino game also contains many disadvantages. Keywords: Islamic Economic, Chip